Quantization and Enhancement of System Frequency Nadir in Power Step Control - WU Shuangxi, LI Wenbo, QIN Yingjie, YAN Binjie, LI Jiapeng, LI Yujun (Shanghai Jiaotong Daxue xuebao)
Converter interfaced power sources have the advantages of flexible and fast response, and the kinetic energy can be released to provide fast system frequency support. However, most of the existing control strategies neglect quantitative analysis of how control strategies affect the frequency nadir, and fail to effectively enhance the frequency nadir under different conditions. Aimed at improving the system frequency nadir, a frequency support strategy based on step power control is proposed. First, the system frequency response under step power control is analyzed, and analytical expressions for the two frequency nadirs following the disturbance are derived. Then, the optimal reference of power step control is determined by considering the kinetic energy which can be released by each wind turbine generator, and a coordinated distribution of the additional power is realized based on these expressions. Finally, a test system is implemented by using MATLAB/Simulink to verify the proposed strategy in numerical simulation.